Effect of PM2.5 for hospitalization of cardiovascular diseases and medical expenses by age group: a nationwide study from the Japanese Registry Of All cardiac and vascular Diseases (JROAD). (25th November 2020) - Kaihara, T; Yoneyama, K; Kuwata, S; Mitarai, T; Watanabe, M; Koga, M; Kamijima, R; Ishibashi, Y; Izumo, M; Tanabe, Y; Higuma, T; Harada, T; et al.
Abstract: Introduction: Although particulate matter with an aerodynamic diameter less than or equal to 2.5 μm (PM2.5) exposure influences cardiovascular events, there is limited knowledge how PM2.5 exposure is associated with cardiovascular hospitalization in Japan. Purpose: We tested the hypothesis that PM2.5 exposure was related to the number of cardiovascular hospitalizations, hospitalization period, and medical expenses. Methods: We included 835, 405 subjects who were admitted to acute care hospitals in Japan. We classified PM2.5 exposure concentration into quintile groups (from low to high in the order of "PM-1" to "PM-5" group). Multilevel mixed-effects Poisson and linear regression analysis were used to estimate the association of PM2.5 exposure concentration with the cardiovascular hospitalization events, duration and medical expenses. We also analyzed those factors classified by age. Results: PM-2, 3, 4, 5 group were positively related to the number of cardiovascular hospitalization events compared with PM-1 group (Table 1). PM-3, 4, 5 group were positively associated with a 0.018, 0.029, and 0.029 (all p<0.001) of the difference of log cardiovascular hospitalization period compared with PM-1 group (p for trend <0.001). These groups were also positively associated with a 0.016, 0.023, and 0.021 (all p<0.001) of the difference of log medical expenses compared with PM-1 group (p for trend <0.001). Analyzed by age group, hospitalization duration was longer (p<0.05) and medical expenses was lower (p<0.05) significantly in super-aging group (over 90 years old) than the group under 64 years old (Figure 1). Conclusions: PM2.5 exposure concentration has harmful effect on not only cardiovascular events but cardiovascular hospitalization period and medical expenses due to big-data in Japan. Medical costs were kept low in comparison with their hospitalization period in subjects over 90 years old. Funding Acknowledgement: Type of funding source: None